Effectiveness of Peer Counseling Interventions on Breastfeeding Outcomes: A Systematic Review and Meta-Analysis - Sümeyye Köse; Enzel Köksaldı; Handan Özcan (Breastfeeding Medicine, 2026)
Objective: This study was conducted to determine the effects of peer counseling on breastfeeding outcomes. Materials and Methods: In this systematic review and meta-analysis study, PubMed, Web of Science, EBSCOhost, Google Scholar, and YÖK Thesis Center databases were searched. The literature search was conducted between January 2025 and February 2026, and no restrictions were applied regarding the year of publication during the search process. Data were combined using meta-analysis and narrative synthesis methods. Findings: A total of 7 studies involving 684 women were included in this systematic review and meta-analysis. The analysis results showed that peer counseling had a statistically significant effect on improving breastfeeding outcomes in mothers (standardized mean difference: −0.951; 95% CI: −1.358 to −0.545; Z = −4.585; p = 0.000; I 2 = 83.59). Conclusion: The findings indicate that peer counseling interventions may improve breastfeeding outcomes. These findings support the integration of peer counseling into breastfeeding support programs and may inform clinical practice and future breastfeeding promotion strategies.